2003
DOI: 10.1136/emj.20.3.228
|View full text |Cite
|
Sign up to set email alerts
|

"Why haven't you taken any pain killers?" A patient focused study of the walking wounded in an urban emergency department

Abstract: Objectives: (1) To assess the proportion of patients of triage category 3-5 presenting to the minor side of an urban emergency department who present without taking prior pain relief, and (2) to describe the reasons why they do not take pain relief for their presenting complaint Method: By patient interview of a convenience sample of 60 adult patients in the setting of an urban emergency department. Results: Fifteen of 60 patients had taken analgesia and 45 of 60 (75%) had not. Sixteen reasons were volunteered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…Enrollment was limited to a convenience sample of 60 adult patients. This study is analogous to ours, as it identified a significant number of patients not attempting analgesic medications before ED arrival, although Nicol and Ashton-Cleary's results were more pronounced (12).…”
Section: Discussionsupporting
confidence: 65%
“…Enrollment was limited to a convenience sample of 60 adult patients. This study is analogous to ours, as it identified a significant number of patients not attempting analgesic medications before ED arrival, although Nicol and Ashton-Cleary's results were more pronounced (12).…”
Section: Discussionsupporting
confidence: 65%
“…Pain is one of the most common presenting complaints in ED and timely and effective analgesia should be one of the major goals of good emergency care. [1][2][3] Untreated severe pain can increase patient fear and anxiety, lead to aggressive behaviour and disturbance of cognition, and have a detrimental effect on physiological parameters. 4,5 However, studies examining analgesia in ED have consistently demonstrated that slow and sub-therapeutic pain relief remains a persistent problem.…”
Section: Introductionmentioning
confidence: 99%
“…The study instrument was a written survey containing 13 questions (). The list of possible reasons for not having taken prior analgesia (Question 4) was derived largely from a UK study in which patients were asked an open‐ended question by an interviewer regarding why they had not taken analgesia 1 . Further possible reasons were added based on the author's experience of reasons given by patients in Australasian EDs.…”
Section: Methodsmentioning
confidence: 99%
“…It was calculated that the study needed to recruit 459 patients, in order that a 15% true difference in primary reason for attending between the two groups (no prior analgesia vs prior analgesia) could be detected with 80% power. A 3:1 ratio of people taking no analgesia before attendance compared with people having taken analgesia was used for this calculation, based on Nichol and Ashton‐Cleary's study in which 75% of participants had not taken analgesia before presentation 1 . In another study 56% took analgesia and 44% didn't 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation